Cyclic loading tests and shear strength of composite joints with steel-reinforced recycled concrete columns and steel beams. (15th November 2019) - Ma, Hui; Dong, Jing; Liu, Yunhe; Yang, Dixiong
Highlights: Seismic performance of the composite joints was investigated by cyclic loading tests. Parameter influence analysis on the seismic behavior of the composite joints. The composite joints have high shear capacity and good deformation capacity. Comparative analysis on the existing formulas of the shear strength for the composite joints. Abstract: Cyclic loading tests were conducted for eight composite joints (five interior joints and three exterior joints) with steel-reinforced recycled concrete (SRRC) columns and steel beams under cyclic loading. The axial compression ratio and recycled coarse aggregate (RCA) replacement percentage were considered as the main design parameters for the above composite joints. The failure process, failure modes, hysteresis loops, skeleton curves, stiffness degradation, storey drift ratio, bearing capacity, ductility and energy dissipation capacity of the joints were presented and analysed in detail. The influence of the design parameters on the mechanical performance of the composite joints under cyclic loading was also investigated. Results showed that the cracking loads of the joints increased with the increase of axial compression ratio. Typical shear failure was the failure mode. The spindle-shaped hysteresis loops of the joints, the ductility coefficients, the elastic-plastic storey drift ratios and the equivalent viscous damping coefficients indicated a relatively good seismic performance. The bearing capacity and stiffness of the joints decreased gradually, while the ductility and energy dissipation capacity of the joints decreased slightly with an increase in the RCA replacement percentage. Additionally, the stiffness degradation of the composite joints accelerated and the energy dissipation capacity and ductility reduced evidently with an increase in the axial compression ratio. Finally, a comparative analysis of each shear strength formula was conducted. The result showed that the formulas of ASCE, AIJ and JGJ138-2001 could predict the shear strength of the joints accurately. This validation indicated that the existing methods are applicable to this group of composite joints.